Digital transformation for Petra tourism: overcoming challenges and seizing opportunities in southern Jordan - Fesail Albahrat; Ibrahim Farhan; Mohd S. Mahafdah; Bashar Khawaldeh; Tareq Hidmi (Cogent Social Sciences)
Petra, inscribed on the UNESCO World Heritage List in 1985, attained the esteemed designation of one of the World’s New Seven Wonders in 2007. It is a quintessential emblem of Jordan and a paramount allure for tourists within the Kingdom. This study aims to scrutinize the foremost tourism motivations among smart application-utilizing tourists, alongside discerning the challenges and impediments encountered by tourists employing digital platforms within Petra city. Utilizing a Digital Elevation Model, weather data, and electronic questionnaires, a random sample of 445 tourists participated in this study by completing an electronic questionnaire. The collected data was then analyzed using IBM SPSS software. Descriptive statistics were employed to investigate the economic and social characteristics of the study participants. Findings reveal that the under-40 age group had the most significant representation, with roughly 71.2% of participants in this category. Where the variable of place of residence, the capital city of Amman accounted for the most significant number of tourists, with a rate of ∼45.1%. Moreover, it was deduced that 88% of tourists utilize smart applications within the study area, primarily leveraging these tools to circumvent overcrowding, economize time and expenses, and navigate effortlessly between locales. The investigation delineated Booking.com as the preeminent application, capturing 23.5% of tourist preference. The study highlights challenges tourists face using smart applications in Petra, including ineffective digital resource utilization and high tourism product prices. To address these issues, it recommends improving internet infrastructure and offering free internet access at all tourist sites.